THE INFLUENCE OF ONLINE MARKETING ON CONSUMER PURCHASE DECISIONS FOR FASHION PRODUCTS: A MARKETING MANAGEMENT PERSPECTIVE - Riza Dessy Nila Ayutika; Helda Rivatul Mahmuddah (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the influence, support, and use of social media by fashion stores Sun on customer involvement and purchase decisions. In addition, this research aims to know and analyze the influence of cultural, personal, and social to decision online purchase decisions of products at Matahari stores. The development of technology, rapid information and communication​, as well as increasing internet awareness and adoption, has push company for integrating social media to in marketing strategy. Utilization of social media as a means of online marketing is expected to increase customer involvement as well as push decision purchase consumers. This study uses a quantitative approach with a sample of as many as 70 respondents. The retrieval technique used​ is purposive sampling, whereas the data collection method uses primary data through a distribution questionnaire. The data obtained was then analyzed using the application SPSS version 25 to test the influence of variables in the research. Research results expected can give a description of the importance of social media in increasing customer involvement, and the decisions of consumers at Matahari fashion stores. In addition, this research also provides a contribution to the development of online marketing strategies in the digital era, especially in the face of growing business​ competition in the retail and e-commerce sectors in Indonesia.